Moderate Molar Incisor Hypomineralization treatment with Microabrasion and Composite Resin - Ozukoc, Can (Eastern Journal of Medical Sciences, 2019)
Molar incisor hypomineralization (MIH) is a very common enamel development defect of the permanent molar and incisor teeth. With the eruption of the permanent molars and incisors at the age of 6-8 years, a significant need for dental treatment emerge. Discolorations and opacities in the maxillary incisors provide the grounds for varied treatment modalities, for managing MIH. Microabrasion and composite resin-based restoration can be considered as the treatment options in moderate to severely affected teeth. Here we present a case report of 12-year-old female patient, who was presented with moderately affected hypomineralized incisor teeth. Further, the patient was treated with the application of microabrasion followed by restoration with composite resin.